Synchronous and Asynchronous Setting in Online Learning to Increase Vocational Students’ Motivation in Mathematics: Comparative Studies - Putrawan, Agus; Ayuni, Dewinta; Apsari, Ratih (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
This study aimed to investigate and compare the factors that influence students' motivation to learn mathematics during synchronous and asynchronous learning. Although many studies related to these two learning models have been carried out, there is still little research on the analysis related to the mathematics learning motivation of vocational program students during the Covid-19 pandemic. The study involved 109 students (Diploma III and Diploma IV) of vocational universities in Bali who were randomly selected and given two different treatments on the same sample. The primary data collection instrument was arranged in a closed-ended questionnaire. Data were analyzed by using the two-sample paired Wilcoxon Signed Rank Test. The results showed that the motivation to learn mathematics for students in the vocational program during asynchronous online learning tended to be better than when the learning process was conducted synchronously. Based on the interviews conducted, there are several causes related to connectivity constraints, the flexibility of study time and discussion, and ease of access to learning resources.Penelitian ini bertujuan untuk menginvestigasi dan membandingkan faktor-faktor yang mempengaruhi motivasi belajar matematika siswa selama mengikuti pembelajaran synchronous dan asynchronous. Meskipun studi terkait kedua model pembelajaran ini telah banyak dilakukan, analisis terkait motivasi belajar matematika mahasiswa program vokasi di masa pandemi Covid-19 masih sedikit ditemukan. Penelitian melibatkan 109 mahasiswa (Diploma III dan Diploma IV) perguruan tinggi vokasi di Bali yang dipilih secara acak dan diberikan dua perlakuan berbeda pada sampel yang sama. Instrumen pengumpulan data primer disusun dalam closed-ended questionnaire. Data dianalisis dengan uji dua sampel berpasangan Wilcoxon Signed Rank Test. Hasil penelitian menunjukan bahwa motivasi belajar matematika mahasiswa program vokasi selama mengikuti pembelajaran daring secara asynchronous cenderung lebih baik dibandingkan dengan synchronous. Berdasarkan wawancara yang dilakukan terdapat beberapa penyebab yang terkait dengan kendala konektivitas, fleksibilitas waktu belajar dan diskusi, serta kemudahan dalam akses sumber belajar.